2019
DOI: 10.3390/ijms21010149
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Proteomic Analyses Reveal the Potential Mode of Action of Chondrocyte Sheets in Hyaline Cartilage Regeneration

Abstract: Chondrocyte sheet transplantation is a novel and promising approach to treating patients who have cartilage defects associated with osteoarthritis. Hyaline cartilage regeneration by autologous chondrocyte sheets has already been demonstrated in clinical research. In this study, the efficacy of polydactyly-derived chondrocyte sheets (PD sheets) as an allogeneic alternative to standard chondrocyte sheets was examined using an orthotopic xenogeneic transplantation model. In addition, the expression of genes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…A heatmap showed that genes related to angiogenesis in the AM_EC group were upregulated compared with those in the AM_EM group, including MMP1 [ 22 ], ESM1 [ 23 ], ANGPT2 [ 24 ] and CYP1B1 [ 25 ] (Fig. 3 a).…”
Section: Resultsmentioning
confidence: 99%
“…A heatmap showed that genes related to angiogenesis in the AM_EC group were upregulated compared with those in the AM_EM group, including MMP1 [ 22 ], ESM1 [ 23 ], ANGPT2 [ 24 ] and CYP1B1 [ 25 ] (Fig. 3 a).…”
Section: Resultsmentioning
confidence: 99%
“…ESM-1 is a proteoglycan involved in angiogenesis and is expressed in the vascular endothelium and adipocytes. DKK-1 is a protein that has an inhibitory effect on the Wnt signaling pathway and is involved in bone metabolism and differentiation [ 29 ]. In this study, the secretion of these humoral factors did not differ significantly between PD sheets and PD sheets-mini and, therefore, we consider that both sheets would have an equivalent effect of cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Polydactyly-derived cell characteristics, including high transforming growth factor (TGF) beta secretion, in juvenile chondrocyte sheets, has been reported [ 25 ]. Hyaline cartilage regenerative capacity using human juvenile polydactyly cartilage-derived chondrocyte sheets was confirmed in an immunosuppressed rabbit osteochondral defect model [ 97 ] and nude rat focal chondral defect model (Kondo et al, submitted). The rat chondral defect model without intentional bone marrow induction particularly demonstrated that regenerated hyaline cartilage forms from human origins with no gaps found at host–donor tissue interfaces ( Figure 2 ).…”
Section: Cell Sheet Engineering —Key Enabling Features Of Thermo-respmentioning
confidence: 99%